A Study On Householders’ Recycling Behavior And The Factors That Determine Their Recycling Intention - Ooi, Hooi Yin (2014)
Proper waste management could reduce environment deterioration. Environment deterioration would subsequently affect quality of human life. Recycling is claimed to be a better solution to this environment issues. Recycling helps to keep environment clean and ensure long-term survival of humankind. There is less study on recycling behavior in developing country such as Malaysia. This study aims to study the householder’s recycling behavior and the factors that determine their recycling intention using Theory of Planned Behavior. A total of 300 self-administered questionnaires were distributed of which 207 of questionnaires were collected back and only 202 were used for data analysis using statistical Package for the Social Sciences (SPSS) and Partial Least Square (PLS).